ผลกระทบของเครือข่ายทางสังคมที่มีต่อระบบทางการเรียนรู้อิเล็กทรอนิกส์ (THE IMPACT OF SOCIAL NETWORKING ON E-LEARNING SYSTEMS) - Phithak, Thawatphong; Khopolklang, Neunghathai; Angskun, Jitimon (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2012)
ปัจจุบันเครือข่ายทางสังคมได้ถูกนำมาประยุกต์ใช้อย่างกว้างขวางในหลายด้าน รวมทั้งการเรียนรู้อิเล็กทรอนิกส์ เหตุที่เป็นเช่นนี้เนื่องมาจากเครือข่ายทางสังคมมีรูปแบบการใช้งานที่หลากหลาย มีความสามารถในการติดต่อสื่อสารระหว่างบุคคลที่โดดเด่น และมีส่วนช่วยในการสร้างความสัมพันธ์ให้กับบุคคลในหลายระดับ แต่อย่างไรก็ตาม ยังไม่พบงานวิจัยที่ศึกษาถึงผลกระทบของเครือข่ายทางสังคมที่นำมาใช้ในงานด้านการเรียนรู้อิเล็กทรอนิกส์อย่างชัดเจน อีกทั้งเว็บไซต์เครือข่ายทางสังคมที่พบในปัจจุบัน ยังมีการจำกัดการเข้าถึงเฉพาะบุคคลที่มีความสนใจในเรื่องที่เฉพาะเจาะจงเท่านั้น งานวิจัยนี้จึงได้พัฒนาระบบทางการเรียนรู้อิเล็กทรอนิกส์ที่มีความคล้ายคลึงกัน จำนวน 2 ระบบ คือ 1) ระบบโนว์เลดจ์แพคเกอร์ และ 2) ระบบโนว์เลดจ์แพคเกอร์ไลต์ ซึ่งระบบแรกจะมีการนำรูปแบบการใช้งานของเว็บไซต์เครือข่ายทางสังคมเข้ามาผสมผสานในตัวระบบ ในขณะที่อีกระบบไม่มี โดยทั้ง 2 ระบบจะถูกนำไปทดลองใช้กับกลุ่มตัวอย่างเพื่อประเมินผลกระทบของเครือข่ายทางสังคมที่มีต่อระบบทางการเรียนรู้อิเล็กทรอนิกส์ ซึ่งจะประเมินผลใน 3 ด้าน คือ ด้านที่ 1 ประเมินความสามารถในการแบ่งปันความรู้ของระบบ พบว่าค่าเฉลี่ยที่ได้จากระบบที่ 1 สูงกว่าระบบที่ 2 ในทุกแง่มุม ได้แก่ จำนวนเนื้อหาที่สร้างขึ้น จำนวนครั้งในการเข้าชมเนื้อหา และจำนวนการแสดงความคิดเห็นในเนื้อหา ด้านที่ 2 ประเมินประสิทธิภาพทางการเรียนรู้ของผู้ใช้ระบบพบว่า ค่าเฉลี่ยคะแนนการทำข้อสอบของผู้ใช้ระบบที่ 1 มีค่าสูงกว่าผู้ใช้ระบบที่ 2 และด้านที่ 3 ประเมินความพึงพอใจของผู้ใช้ที่มีต่อความสามารถด้านปฏิสัมพันธ์ของระบบ พบว่าทั้งสองระบบ ผู้ใช้มีความพึงพอใจในระดับมาก โดยจุดเด่นของระบบคือ ด้านประสิทธิผลและความเหมาะสมในการใช้งาน และจุดด้อย คือ ด้านความปลอดภัย คำสำคัญ: เครือข่ายทางสังคม การเรียนรู้อิเล็กทรอนิกส์ การแบ่งปันความรู้ Currently, the social networking has been widely applied in various areas, including the e-learning. It is due to the fact that the social networking has various forms of uses, an outstanding ability in interpersonal communication, and an agent in making relation between people in several levels. However, none of researches have distinctly studied about the impact of social networking on applying in the e-learning. In addition, the existing social-networking sites limit individual access to a specific subject. This research developed two similar e-learning systems in order to evaluate the impact of social networking in e-learning systems, which are Knowledge Packer System and Knowledge Packer Lite System. The first system, called Knowledge Packer System, integrated the social networking; while the second system, Knowledge Packer Lite System, did not integrate. After both systems have been created, they are tested with a representative sample of end users and then the experimental results are evaluated in three aspects. The first aspect evaluated an ability of system in knowledge sharing. The experimental results found that the mean of the first system was higher than the second system in every aspect, such as the number of created contents, the number of content visiting and the number of comments in contents. The second aspect evaluated the learning efficiency of users which the results showed that the mean of test scores of the first system was higher than that of the second system. The third aspect evaluated the user gratification in terms of user interaction with the systems. The results indicated that both systems provided a high level in the user gratification. The outstanding of systems is effectiveness and suitability of uses; whereas the weak point of systems is security. Keywords: Social Networking, E-Learning, Knowledge Sharing